IMPROVING STUDENTS’ CRITICAL THINKING SKILLS BY USING PROJECT-BASED LEARNING (PBL) - Suhermanto, Hadi; Safnil; Arono (Corolla International Conference, 2022)
This research is focused on fostering students’ critical thinking through Project-Based Learning. This research sought to know whether the Project-Based Learning is effective for English Study Program students at IAIN Curup. The design of the research was quasi-experimental research which wanted to find out the effect of Project Based Learning towards Critical Thinking of IAIN Curup. To know students’ Critical Thinking, this research uses Critical Thinking test. There are three pre-tests and post-tests. The pre-test were used to see students’ Critical Thinking before having treatment and post-test are used to see the differences on students critical thinking after giving treatments. The subjects were the students of English Study Program at IAIN Curup who took Speaking class. The data found that Project Based Learning has a significant effect on students' Critical Thinking skills. This conclusion can be seen based on the analysis that has been done where t observed > t table. Thus, it can be concluded that Critical thinking skills can be increased by using Project Based Learning method.